Slant Curves in the Unit Tangent Bundles of Surfaces. (5th December 2013) - Hou, Zhong Hua; Sun, Lei
Abstract : Let ( M, g ) be a surface and let ( U ( T M ), G ) be the unit tangent bundle of M endowed with the Sasaki metric. We know that any curve Γ ( s ) in U ( T M ) consist of a curve γ ( s ) in M and as unit vector field X ( s ) along γ ( s ) . In this paper we study the geometric properties γ ( s ) and X ( s ) satisfying when Γ ( s ) is a slant geodesic.